The first in the Left-bank of Middle Cis-Dnipro Area the National Natural Park "Biloosersky" (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
A preliminary results of floristic and coenotic analysis pf phytodiversity of Biloozersky National Natural Park are presented. A list of rare (Epipactis helleborine (L.) Crantz, Stipa borysthenica Klokov ex Prokud., Astragalus dasyanthus Pall., Adonis vernalis L., Pulsatilla bohemica (Skalický) Tzvelev, Iris sibirica L., Trapa natans L.) and regional rare species, and rare plant communities of the park (Nuphareеta luteae, Nymphaeeta albae, Salvinieta natantis, Trapeta nanantis) are given.
Keywords: National Natural Park